Appraisal survey of the knowledge, attitudes, and behaviors of Jordanian society toward diet and nutrition during COVID-19 era - Omar Alhaj; Hiba F. Al-Sayyed; Maha M. AlRasheed; Haitham Jahrami (SAGE Publishing, 2021)
Introduction: This study aimed to evaluate the knowledge, attitudes, and behavior (KAB) of the Jordanian society toward nutrition and diet during the COVID-19 era. Design and methods: This study is an observational, cross-sectional study using a structured, validated, reproducible, self-administered online Arabic questionnaire. KAB of the study participants was assessed via a web-based, structured, validated, reproducible Arabic questionnaire. The tool for the assessment of the KAB was composed of 33-closed-ended multi-answer questions. Results: A total of 672 people were surveyed, 70.2% were between 18 and 34, and 69.5% were females. Participants have paid little attention to the healthfulness of their diet in the last year. The majority of participant's attitudes towards using different approaches to manage weight in the next year were: eating smaller portions for weight management, tracking to maximize the amount of time of physical activity, and substituting lower-calorie foods for full-calorie alternatives. Only tenth of participants utilize the time to perform physical activity. The majority made changes to their diet and exercise, and strictly follow commitment in connection with planning for the following year. Conclusions: Educators, legislative, food manufacturers, household heads, and policymakers are called upon to improve Jordanians' KAB on nutrition and diet. Furthermore, Jordanian nutrition and diet behavior can be invested to improve the dietary interventions designed by nutrition and dietetics professionals.